A review on grid power quality improvement in wind energy system using STATCOM with BESS (International Journal of Engineering and Computer Science, 2016)
The sources such as wind power and solar power are expected to be promising energy sources when it is connected to the power grid. The wind generators have a significant impact on the power quality, voltage profile and the power flow for customers and electricity suppliers. The power exhausted from above energy sources varies due to environmental conditions. Due to the fluctuation in nature of the wind, the wind power injection into an electric grid affects the power quality. The influence of the wind sources in the grid system concerns the power quality such as the reactive power, active power, voltage variation, harmonics and electrical behaviour in switching operation[1]. Demonstration of a grid side  connected wind turbine is considered here with the problem arise due to the above system. At the point of common coupling a Static Synchronous Compensator with Battery Energy Storage System-STATCOM/BESS, can regulate four-quadrant active and reactive power, which is an ideal scheme to solve problems of wind power generation. As the power from wind generation varies with time so the battery energy storage used to maintain constant real power comprehensively from varying wind power. The power generated through wind generator can be stored in the batteries at low power demand hours[2-4]. The combination of battery storage with wind energy generation system will synthesize the output waveform by absorbing or injecting reactive power and enable the real power flow required by the load. The control strategy can coordinate charge or discharge of batteries with reactive power compensation of STATCOM, and balance the batteries capacity. If required, amount of energy consumed or given to the grid can be observed through an online smart meter connected in the circuit.